A case report: Delayed gallstone abscess formation 10 years post-cholecystectomy. (2020) - Quinn, Erina; Capanegro, James; Hartigan, Joseph
Highlights: Successful removal of gallstones are important to prevent the formation of gallstone abscess and infection. An increase of reports of gallstone abscess formation shows the importance of awareness in the surgical community of the occurrence and proper treatment techniques. Proper treatment techniques include abscess drainage either surgically or non-invasive and if possible laparoscopic repair of gallstone abscess. Abstract: Introduction: Retained gallstones post-cholecystectomy act as a nidus for abscess formation. It is unusual for intraabdominal abscesses to remain asymptomatic due to its propensity to cause inflammation and irritation to the peritoneum. Presentation of case: A 73-year-old female presented with acute onset of right-sided abdominal pain and fever. Her past surgical history was significant for a cholecystectomy in 2010, hysterectomy, and partial nephrectomy. She was diagnosed with an intraabdominal abscess secondary to a retained gallstone post-cholecystectomy. She underwent laparoscopic surgery to drain and remove the abscess. The patient's abdominal pain improved, remains afebrile, and is passing stool regularly. Discussion: Gallbladder perforation is common and is dependent on the integrity of the gallbladder and surrounding structures. It is unusual for an intra-abdominal abscess to develop so late following gallstone spillage. This example brings to light the potential long-term sequelae of gallbladder perforation and future complications. Conclusion: This case highlights the importance of irrigation of the peritoneal cavity and retrieval any spilled gallstones during surgery in the event of gallbladder perforation.